Absence of Cold-Inducible RNA-Binding Protein (CIRP) Promotes Angiogenesis and Regeneration of Ischemic Tissue by Inducing M2-Like Macrophage Polarization - Matthias Kübler; Sebastian Beck; Silvia Fischer; Philipp Götz; Konda Kumaraswami; Hellen Ishikawa-Ankerhold; Manuel Lasch; Elisabeth Deindl (Biomedicines, 2021)
Cold-inducible RNA-binding protein (CIRP) is an intracellular RNA-chaperone and extracellular promoter of inflammation, which is increasingly expressed and released under conditions of hypoxia and cold stress. The functional relevance of CIRP for angiogenesis and regeneration of ischemic muscle tissue has never been investigated and is the topic of the present study. We investigated the role of CIRP employing CIRP deficient mice along with a hindlimb model of ischemia-induced angiogenesis. 1 and 7 days after femoral artery ligation or sham operation, gastrocnemius muscles of CIRP-deficient and wildtype mice were isolated and processed for (immuno-) histological analyses. CIRP deficient mice showed decreased ischemic tissue damage as evidenced by Hematoxylin and Eosin staining, whereas angiogenesis was enhanced as demonstrated by increased capillary/muscle fiber ratio and number of proliferating endothelial (CD31+/BrdU+) cells on day 7 after surgery. Moreover, CIRP deficiency resulted in a reduction of total leukocyte count (CD45+), neutrophils (myeloperoxidase, MPO+), neutrophil extracellular traps (NETs) (MPO+/CitH3+), and inflammatory M1-like polarized macrophages (CD68+/MRC1-), whereas the number of tissue regenerating M2-like polarized macrophages (CD68+/MRC1-) was increased in ischemic tissue samples. In summary, we show that the absence of CIRP ameliorates angiogenesis and regeneration of ischemic muscle tissue, most likely by influencing macrophage polarization in direction to regenerative M2-like macrophages.